Sovereign debt and socio-economic rights beyond crisis : the neoliberalisation of international law / Emma Luce Scali. - Scali, Emma Luce, 1982- (Cambridge University Press, 2022)
This book offers a distinctive critical discussion of the relationship between sovereign debt and socio-economic human rights in the context of the contemporary global neoliberal economic order, going beyond strictly 'post-crisis' approaches and emphasising the structural character and consistent growth of public and private indebtedness. It reflects on the implications of mounting debt for the actual ability of States to realise human rights in a world of escalating indebtedness, inequality and insecurity. It expands existing definitions of neoliberalism by reflecting in particular on neoliberalism's epistemological underpinnings, and provides a comprehensive and systematic analysis of the 2009 Greek debt crisis and the main elements of post-crisis developments in international and EU law, arguing that the 'neoliberalisation of law' has essentially been advanced in the wake of the Eurozone debt crisis.